Comparison on the fatty acid profiles of liver, subcutaneous fat and muscle from feedlot steers finished on diets supplemented with or without cinnamaldehyde or monensin. (15th July 2014) - He, Maolong; Jia, Jianjie; Yang, Wenzhu
Abstract BACKGROUND Cinnamaldehyde (CIN) is the main active component of cinnamon (Cinnamomum cassia) oil and has been tested as alternative feed additive in cattle production. Little information was available on the effect of dietary CIN in comparison to monensin (MO) on beef fatty acid (FA) profile. This study analyzed FA profiles of liver, subcutaneous fat and pars costalis diaphragmatis (PCD) muscle obtained from steers (n = 70) finished on diets: control, a barley grain–silage feedlot diet; 330 mg/head.day MO; and 400, 800 or 1600 mg/head.day CIN treatments. RESULTS Inclusion of MO or CIN did not affect total saturated, unsaturated, polyunsaturated FA and individual FA in the various tissues with exceptions that proportion of palmitic acid in PCD muscle was increased by 800 mg/steer.day CIN (P < 0.05). There were positive correlations (P < 0.05) on oleic, linoleic, conjugated linoleic acid (CLA)‐c9, t11 and 18:1‐t10 between the subcutaneous fat and PCD muscle, and on α‐linolenic acid, CLA‐c9, t11 and 18:1‐t10 between PCD muscle and liver, whereas correlations on the FA between the subcutaneous fat and liver were not significant except for 18:1‐t10 (P < 0.01). CONCLUSION The results indicate that the supplementation of CIN and MO to feedlot diet has limited effect on beef FA profiles. © 2014 Her Majesty the Queen in Right of Canada Journal of the Science of Food and Agriculture © 2014 Society of Chemical Industry